The Effectiveness of Product sampling Communication by Primagama Surabaya - Nuris Alfan Fikri (Pancaran Pendidikan, 2018)
This study is aimed to analyze the effectiveness of product sampling as a one of sales promotion tools in tutoring agency. Product sampling in education agency has become a favorite method to introduce their services to customers, including Primagama. The effectiveness is measured based on communicative objectives, they are attention, understanding, persuasion, and purchase intention. Scoring is used by implementing likert scale. The result shows that product sampling is effective in three communication factors (understanding, persuasion, and purchase intention) but less effective in one communication factor (attention).